2020
DOI: 10.5937/ejae17-19472
|View full text |Cite
|
Sign up to set email alerts
|

Does urbanization intensify carbon emissions in Nigeria?

Abstract: This study examines the urbanization and CO2 emissions nexus in Nigeria using the Autoregressive Distributed Lag (ARDL) method to analyze the annual time series data spanning from 1974 to 2015. Findings suggest that urbanization, GDP, energy use, and carbon emissions are strongly and positively correlated, while trade and carbon emissions exhibit a weak and negative correlation. The ARDL result shows a negatively significant short-term and long-term connection between urbanization and carbon emission in the Ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…Thus, the outcome reveals that a 1% change in the trajectory of URB will lead to a decline of ENVP by 0.528%. Hence, this study put forward that policymakers should assist in streamlining urban population areas in the selected economies by upgrading renewable energy use to ensure a faster decline of ENVP and support the economies' long-term development [ 90 , 91 ].…”
Section: The Empirical Results and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Thus, the outcome reveals that a 1% change in the trajectory of URB will lead to a decline of ENVP by 0.528%. Hence, this study put forward that policymakers should assist in streamlining urban population areas in the selected economies by upgrading renewable energy use to ensure a faster decline of ENVP and support the economies' long-term development [ 90 , 91 ].…”
Section: The Empirical Results and Discussionmentioning
confidence: 99%
“…Urbanization denotes the gradual shift of population from rural areas to urban places, the respective decline in the percentage of the populace dwelling in rural areas, and the modalities in which the communities adapt to changes [ [88] , [89] , [90] , [91] ]. Studies have shown that population growth within urban vicinities impacts environmental quality through increased tension on limited resources through energy consumption [ 92 ].…”
Section: Literary Work and Hypothesis Developmentmentioning
confidence: 99%
See 3 more Smart Citations